Ad Hoc Network Performances for Hybrid Social Networks - Filiposka, Sonja; Trajanov, Dimitar (My University, 2008)
Ad hoc networks provide means for information sharing for a group of users. Thus, care must be taken that a proper model of the end-to-end communication is used. In order to model a real-life situation, we use a unifying hybrid social network model that captures the scale-free property and small-world effect that appear when viewing the graph that corresponds to the user interaction. Several hybrid networks are investigated and certain interesting behaviors are shown
Keywords: ad hoc network, unifying hybrid model, traffic pattern, scale free property, small world effect